Effects of genetic polymorphisms in body mass index according to dietary exposure to bisphenols and parabens. (April 2022) - Ramírez, Viviana; Robles-Aguilera, Virginia; Salcedo-Bellido, Inmaculada; Gálvez-Ontiveros, Yolanda; Rodrigo, Lourdes; Martinez-Gonzalez, Luis Javier; Monteagudo, Celia; Álvarez-Cubero, María Jesús; Rivas, Ana
Abstract: A growing body of evidence supports that more than 900 single nucleotide polymorphisms (SNPs) and exposure to endocrine disrupting chemicals, such as bisphenols and parabens, are important contributors to the development of obesity. The aim of this study was to evaluate the way in which fat mass and obesity-associated gene ( FTO ) rs9939609 and leptin receptor ( LEPR ) rs9436303 variants contribute to variability in body mass index (BMI) according to estimated dietary exposure of bisphenols and parabens. This cross-sectional study included 101 Spanish participants (16–24 years). SNP genotyping assays were performed through quantitative PCRs (qPCRs) using Taqman® probes. Dietary exposure to bisphenols and parabens was calculated from food frequency questionnaire and chemical determination in food samples by ultra-high performance liquid chromatography-tandem mass spectrometry system. Linear regression models were conducted to address the association of genetic variants and BMI according to levels of bisphenols/parabens exposure. Risk G allele of LEPR rs9436303 was significantly positively associated with BMI (exp (β) = 1.20, 95% CI: 1.04–1.38, p = 0.011). In participants highly exposed to bisphenols, the LEPR rs9436303 G allele was related to a significant increased BMI (exp (β) = 1.27, 95% CI: 1.03–1.57, p = 0.024). A more relevant trend was observed with high exposure to parabens (exp (β) = 1.33, 95% CI: 1.08–1.63, p = 0.009). We provide the first evidence that interaction between LEPR polymorphism and dietary intake of bisphenols and parabens may be responsible for an increased BMI, suggesting a potential effect in obesity. Moreover, we proposed LEPR rs9436303 as a genetic marker of susceptibility to excess weight induced by exposure. Graphical abstract: Image 1 Highlights: LEPR rs9436303 variant allele G significantly contributes to increased BMI. Combined effect of LEPR rs9436303 and dietary exposure to bisphenols/parabens in BMI variability is proposed in present work. LEPR rs9436303 variant proposed as a genetic marker for susceptibility to obesity in exposed population.